A CFD investigation on the flow around a low aspect ratio vertical cylinder: modeling free surface and turbulent effects. - Lopes, Pedro Paludetto Silva de Paula (2019)
The fow around bluff bodies is an essential topic in fuid dynamics. This fow is characterized by large vortical fow regions separating from the surface of the bluff body, and they cause oscillating drag and lift forces on the structure. The fow around an infinite long cylinder is a well-known case being studied in the literature. However, a cylinder with low aspect-ratio piercing the free surface has not been studied much although such an arrangement can be found in many floating offshore structures. In this thesis the results of CFD calculations are presented for a fixed, free surface piercing cylinder with an aspect-ratio L/D equals to 2. The Reynolds number was equal to 4:3 x 104 indicating that the flow is in the sub-critical turbulent regime. An extensive methodology of verication and validation is followed to investigate the reliability of the results. To investigate the effect of the free surface on the calculated hydrodynamic loads, two approaches have been considered: a double-body symmetry condition and an interface capturing Volume-of-Fluid (VoF) method. Additionally, two turbulence models are investigated: a two-equation turbulence model; a non-linear Explicit Algebraic Reynolds Stress Model (EARSM); and the Improved Delayed Detached Eddy Simulation (IDDES) turbulence model. The results are presented in terms of integral results (drag and lift coefficients) and flow visualizations. Based on the results of the cases in which the free surface was modeled as a double body symmetry boundary condition, it is concluded that the model is not suitable for this type of flow as the model damps out the flow dynamics due to over-production of eddy-viscosity. Hence, the characteristic oscillating lift forces are not captured using this turbulence model. However, this turbulence model showed good agreements regarding the flow fields in comparison with experimental PIV measurements. Results of the case modeled with EARSM turbulence model shows better agreement with the experimental results compared with the turbulence model. In the cases where the free-surface is considered, results with the EARSM turbulence model show similar results for the drag forces whereas the lift uctuations were one order of magnitude smaller, compared with the double body case. Lastly, the results using the IDDES turbulence model and free-surface VoF modeling are shown to produce the best comparison with the experimental results, regarding both, integral values and flow field results.